Stories, Statistics, and Memory - Thomas Graeber; Christopher Roth; Florian Zimmermann (Center for Economic Studies and ifo Institute (CESifo), 2022)
For most decisions, we rely on information encountered over the course of days, months or years. We consume this information in various forms, including abstract summaries of multiple data points – statistics – and contextualized anecdotes about individual instances – stories. This paper proposes that we do not always have access to the full wealth of our accumulated information, and that the information type – story versus statistic – is a central determinant of selective memory. In controlled experiments we show that the effect of information on beliefs decays rapidly and exhibits a pronounced story-statistic gap: the average impact of stories on beliefs fades by 33% over the course of a day, but by 73% for statistics. Consistent with a model of similarity and interference in memory, prompting contextual associations with statistics improves recall. A series of mechanism experiments highlights that the lower similarity of stories to interfering information is the key driving force behind the story-statistic gap.
Keywords: 330; memory; belief formation; stories; narratives; statistical information